View of the suburbs Weissgärber and Landstrasse in Vienna - Leitner, Anton (engraver):::Creator::::::::::::; Wett, J. (artist):::Contributor:::::::::::: (Vienna; Austria; P. P. Mechitaristen)
Engraving with a panoramic view of Vienna